A next generation sequencing approach with a suitable bioinformatics workflow to study fungal diversity in bioaerosols released from two different types of composting plants - Mbareche, Hamza; Veillette, Marc; Bonifait, Laetitia; Dubuis, Marie-Eve; Benard, Yves; Marchand, Geneviève; Bilodeau, Guillaume J.; Duchaine, Caroline (The Science of the total environment, 2017)
Composting is used all over the world to transform different types of organic matter through the actions of complex microbial communities. Moving and handling composting material may lead to the emission of high concentrations of bioaerosols. High exposure levels are associated with adverse health effects among compost industry workers. Fungal spores are suspected to play a role in many respiratory illnesses. There is a paucity of information related to the detailed fungal diversity in compost as well as in the aerosols emitted through composting activities. The aim of this study was to analyze the fungal diversity of both organic matter and aerosols present in facilities that process domestic compost and facilities that process pig carcasses. This was accomplished using a next generation sequencing approach that targets the ITS1 genomic region. Multivariate analyses revealed differences in the fungal community present in samples coming from compost treating both raw materials. Furthermore, results show that the compost type affects the fungal diversity of aerosols emitted. Although 8 classes were evenly distributed in all samples, Eurotiomycetes were more dominant in carcass compost while Sordariomycetes were dominant in domestic compost. A large diversity profile was observed in bioaerosols from both compost types showing the presence of a number of pathogenic fungi newly identified in bioaerosols emitted from composting plants. Members of the family Herpotrichiellaceae and Gymnoascaceae which have been shown to cause human diseases were detected in compost and air samples. Moreover, some fungi were identified in higher proportion in air compared to compost. This is the first study to identify a high level of fungal diversity in bioaerosols present in composting plants suggesting a potential exposure risk for workers. This study suggests the need for creating guidelines that address human exposure to bioaerosols. The implementation of technical and organizational measure should be a top priority. However, skin and respiratory protection for compost workers could be used to reduce the exposure as a second resort. [Display omitted] •ITS Next-generation sequencing approach to study fungal diversity in bioaerosols released from composting plants is presented•A bioinformatics workflow is described for the treatment of the raw sequencing data and for the fungal diversity analyses•Differences in the fungal community in bioaerosols from compost treating different raw materials were observed•A number of pathogenic fungi newly identified in compost bioaerosols•This study suggests the need for creating guidelines addressing respiratory protection of workers in composting plants.